Factores Ambientales y Estres en Madres de Neonatos Hospitalizados en Unidades de Cuidados Intensivos e Intermedios I, 2015 - Banda Macedo, Cynthia Pamela (2016)
Descriptive correlational research with quantitative approach, realized in Víctor Lazarte Echegaray, 2015 Hospital; aimed at determining the environmental factor: unit sounds, child’s appearance and behavior, child relationship, mothers’ role, and behavior-communication with personnel according to higher stress generation in mothers of newborns hospitalized in the First Intensive and Intermediate I Care Unit. Sample represented by 32 mothers. Data wascompiled with THE STRESSOR SCALE FOR MOTHERS: NEONATAL INTENSIVE CARE UNIT using the correlation coefficient of Pearson. It concludes: Environmental factor aspects and sounds of the unit, mostly generates an extremely stressful and very stressful (50% and 43.55% respectively) level; Appearance and child behavior, mostly generates an extremely stressful and very stressful (68.75% and 18.75% respectively) level; Relationship to child and maternal role, generates a high level of stress in their entirety, where 81.25% is an extremely stressful level and 18.75% a very stressful level; Behavior and communication with the staff as generating greater stress in mothers of hospitalized infants generates a high level of stress in their entirety, where 62.5% is an extremely stressful level and 37.5% a very stressful level. It concludes: Environmental factor aspects and sounds of the unit, mostly generates an extremely stressful and very stressful (50% and 43.55% respectively) level; Appearance and child behavior, mostly generates an extremely stressful and very stressful (68.75% and 18.75% respectively) level; Relationship to child and maternal role, generates a high level of stress in their entirety, where 81.25% is an extremely stressful level and 18.75% a very stressful level; Behavior and communication with the staff as generating greater stress in mothers of hospitalized infants generates a high level of stress in their entirety, where 62.5% is an extremely stressful level and 37.5% a very stressful level. Keywords: Generation of stress and environmental factors.